OpenStudy (anonymous):

5-(t=3)=-1+2(t-3)

5 years ago
OpenStudy (directrix):

5-(t=3)=-1+2(t-3) --> There are two = symbols here. Please clarify the problem. Thanks.

5 years ago
OpenStudy (anonymous):

the equation should have only one equal sign

5 years ago
OpenStudy (anonymous):

if the equation is 5-(t-3)=-1+2(t-3) then, 5-t+3=-1+2t-6 and you can solve t by addition property of equality

5 years ago
OpenStudy (directrix):

@rafeds08 Yes 5-(t-3)=-1+2(t-3) --> Use Distributive Property 5-t+3=-1+2t-6 8 - t = -7 + 2t Next, get the t terms together on one side and the constant terms on the other

5 years ago